In silico study of the active compounds in bitter melon (Momordica charantia L) as antidiabetic medication - Ruswanto, Ruswanto; Mardianingrum, Richa; Lestari, Tresna; Nofianti, Tita; Tuslinah, Lilis; Nurmalik, Dudi (Universitas Ahmad Dahlan, 2018)
Antidiabetic are many drugs available in the market, but most medications have side effects that are relatively high and cause toxicity, so it needs tobe develoved search of new drug compounds were more potent drugs with side effects as low. Various research have shown that bitter melon (Momordica charantia L) has an effect antidiabetic. But it is not known specifically as antidiabetic compounds that act on bitter melon (Momordica charantia L). This study was conducted to predict the active compounds of bitter melon (Momordica charantia L)potent as antidiabetic in silico, through the molecular docking, Drug scan, PreADMET and molecular dinamics simulation. The results of the 26 active compound bitter melon (Momordica charantia L) obtained one potential compounds that are active against nuclear reseptor RORÎ± that is goyaglikosida-h and more potent than Rosiglitazon